2005
DOI: 10.1093/jnci/dji019
|View full text |Cite
|
Sign up to set email alerts
|

Sun Exposure and Mortality From Melanoma

Abstract: Sun exposure is associated with increased survival from melanoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
266
3
17

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 389 publications
(307 citation statements)
references
References 15 publications
21
266
3
17
Order By: Relevance
“…That finding is dependent on the criteria used to define a low level of sun exposure. The criterion used in this study was similar to those reported by Berwick et al 22 This might be one of the most crucial points of this study since the level of sun exposure has always been particularly difficult to quantify. Taking into account that the patients were born and raised in Spain, a sunny country, it is possible that some periods of sun exposure may have been unintentionally omitted by the patients.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…That finding is dependent on the criteria used to define a low level of sun exposure. The criterion used in this study was similar to those reported by Berwick et al 22 This might be one of the most crucial points of this study since the level of sun exposure has always been particularly difficult to quantify. Taking into account that the patients were born and raised in Spain, a sunny country, it is possible that some periods of sun exposure may have been unintentionally omitted by the patients.…”
Section: Discussionmentioning
confidence: 74%
“…We classified patients according to sun exposure using a similar criterion to the one described by Berwick et al 22 Specifically, we considered patients with a low level of sun exposure, those patients who had never had sunburns, who had never sunbathed during the summertime, who had spent less than 10 days per year doing outdoor recreational or occupational activities and who had never lived in tropical countries. All patients were interviewed by the same interviewer using a standardized questionnaire.…”
Section: Patientsmentioning
confidence: 99%
“…The rising incidence makes this cancer an issue of ever increasing clinical and economic importance and research interest (Garland et al, 2003;Tucker and Goldstein, 2003;Berwick et al, 2005). The identification of new prognostic markers may help to better distinguish low from high-risk disease apart from the classical histopathologic and clinical criteria (Carlson et al, 2005) and may offer new targets for therapy.…”
mentioning
confidence: 99%
“…[11][12][13] The importance of vitamin D is reflected by the fact that CMM patients had deficient and insufficient prediagnostic vitamin D 3 levels [14] and survived longer if they got regular sun exposures. [15] Furthermore, outdoor workers have twice the vitamin D 3 levels as indoor workers [16] and they have about half the risk for getting CMM. [17] And along with providing another apoptotic pathway for melanoma cells through the vitamin D 3 receptor, [13] vitamin D 3 boosts the immune system by enabling T cells to become activated so they can kill virally infected and malignant cells.…”
Section: Introductionmentioning
confidence: 99%